The Relationship Between Environmental Conditions and Production of Kurau Fish (Eleutheronema tetradactylum) In Teluk Pambang, District of Bengkalis (Jurnal Kajian Lingkungan, 2013)
This study aims to determine of Kurau fish (Eleutheronema tetradactylum) production and environmental factors that cause a decrease in kurau fish production in the Teluk Pambang waters, Bengkalis. The results showed that the level of fish production Kurau (Eleutheronema tetradactylum) in the waters of the Teluk Pambang, Bengkalis in 2012 amounted to 9,273 kg, while the maximum potential of sustainable (MSY) kurau 4,067 kg of fish. Thus there has been in excess utilization at 228%. The main factors causing the decline of Kurau fish production is fishing effort by trip 894 (170.8%) which exceeds the optimum effort 497 trips/ year. Furthermore, the causes of the decline of Kurau fish production is also influenced by the high value of the Total Suspended Solid (TSS) that is equal to 89 mg/l and chemical parameters (CO2) of 12.4 mg/L.Keywords: environment, production, kurau fish (Eleutheronema tetradactylum)